Barodontalgia:- Revealing the Unreveaing - Aravindha Babu.N, Sudakshina Mukherjee2 , N. Anitha3 , K.M.K.Masthan4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Barodontalgia is a pain due to pressure difference. Here in this review article, pathophysiology, manifestation,associated conditions and treatment guidelines of this rare symptom have been discussed. It is often a flareup of preexisting sub clinical oral diseases. Deep sea divers, air crew members especially of fighter jets oftensuffer from these due to frequent altitude difference and with it the pressure difference. This often pose agreat challenge to dental surgeons who sometimes fail to found the exact ill tooth of problem so managementbecomes problematic.